A systematic review evaluating loneliness assessment instruments in older adults - Bugallo-Carrera, César; Dosil-Díaz, Carlos; Anido-Rifón, Luis; Pacheco-Lorenzo, Moisés; Fernández-Iglesias, Manuel J.; Gandoy-Crego, Manuel (Frontiers in Psychology, 2023)
Introduction and objectives. Old age is a period in life during which people commonly undergo experiences and changes that may lead to a feeling of loneliness usually followed by negative physical and mental manifestations. In this systematic review, we aimed at exploring the available instruments to assess loneliness in older adults. Methods. The search of articles was done in the Web of Science, Medline, and PsycINFO following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Once assessed the quality of the articles, we examined the psychometric properties of the instruments focusing of reliability, validity, and main conclusions. Results. Twenty-seven articles published between 1996 and 2021 were included in this review. Conclusions. To date there are few instruments to assess loneliness in older adults and the available ones lack reliability and validity.